Creating a sustainable competitive position : ethical challenges for international firms - Ghauri, Pervez N., 1948-; Elg, Ulf; Hånell, Sara Melén, 1978- (International business and management series ;, 2023)
The ebook edition of this title is Open Access and freely available to read online. The importance of ethical practices and a sustainable competitive position is being increasingly emphasised by all types of business and across all industries. The chapters collected in Creating a Sustainable Competitive Position discuss how international firms work with sustainable strategies and their relationship with the society and environment while exploring the different opportunities and challenges. While good transparent ethical behaviour improves a company's reputation and thus competitive position, unethical and/or illegitimate behaviour such as environmental exploitation and corruption can damage a firm's global reputation. Several case studies from different markets demonstrate how this sustainable competitive position can be achieved by international firms operating in a global market. Creating a Sustainable Competitive Position includes research-based cases highlighting different sustainability challenges as well as theory-based discussions around how firms can manage a multi-stakeholder perspective in relation to performance. The extensive research within this volume of International Business and Management makes it an important read for both managers, leaders and researchers in the area of strategy, offering ways to stay ahead of the competition.